Treatment of generalized granuloma annulare – a systematic review. (4th February 2015) - Lukács, J.; Schliemann, S.; Elsner, P.
Summary Granuloma annulare (GA) is a benign inflammatory skin disease. Localized GA is likely to resolve spontaneously, while generalized GA (GGA) is rare and may persist for decades. GGA usually is resistant to a variety of therapeutic modalities and takes a chronic course. The objective of this study was to summarize all reported treatments of generalized granuloma annulare. This is a systematic review based on MEDLINE, Embase and Cochrane Central Register search of articles in English and German and a manual search, between 1980 and 2013, to summarize the treatment of generalized granuloma annulare. Most medical literature on treatment of GGA is limited to individual case reports and small series of patients treated without a control group. Randomized controlled clinical studies are missing. Multiple treatment modalities for GGA were reported including topical and systemic steroids, PUVA, isotretinoin, dapsone, pentoxifylline, hydroxychloroquine, cyclosporine, IFN‐γ, potassium iodide, nicotinamide, niacinamide, salicylic acid, dipyridamole, PDT, fumaric acid ester, etanercept, infliximab, adalimumab. While there are numerous case reports of successful treatments in the literature including surgical, medical and phototherapy options, well‐designed, randomized, controlled clinical trials are required for an evidence‐based treatment of GGA.